2021
DOI: 10.3390/jmse9020196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seawater Ageing on Fracture Toughness of Stitched Glass Fiber/Epoxy Laminates for Marine Applications

Abstract: Composite materials are used in various industries such as marine, aircraft, automotive, etc. In marine applications, composites are exposed to seawater, which can affect their mechanical properties due to moisture absorption. This work focuses on the durability of composite materials under the short-term effect of seawater ageing. The specimens were prepared from glass fiber/epoxy using a hand lap-up method and stitched in the z-direction with Kevlar fiber. The specimens were submerged in seawater for 24 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, if the edge of the material is subject to the water as well, the graph shown in Figure 5 can be used to estimate Dl [14]. The moisture concentration at any instance can be calculated using equation (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if the edge of the material is subject to the water as well, the graph shown in Figure 5 can be used to estimate Dl [14]. The moisture concentration at any instance can be calculated using equation (6).…”
Section: Resultsmentioning
confidence: 99%
“…A Fickian diffusion is a model that describes the absorption and desorption of substances that will flow through the material, in this case, seawater, during the time [12]. In other words, it describes the change of substance concentration with respect to time, following the second law of Fick in one dimension described in equation (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, the utilisation of marine composites has grown in popularity [1][2][3][4][5]. This has been considered both as full thermoplastic composite pipes (TCP) or as hybrid composite structures [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that composite materials can survive seawater ingress at different levels based on individual material properties. Hassan et al [63] studied the effect of seawater on marine composites by using glass fibre/epoxy laminates to investigate fracture toughness. Bearing this information in mind, the application of composites can be deployed to improve the material strength, flexibility, stiffness ratio and other mechanical behaviours of the marine bonded hoses.…”
Section: Introductionmentioning
confidence: 99%